Care workers in Argentina: At the crossroads of labour market institutions and care services - Esquivel, Valeria Renata (2017)
In Argentina, one-third of all employed women, but only 3 per cent of all employed men, are care workers. Their relative pay and working conditions depend not only on applicable labour market regulations (and enforcement) but also, crucially, on the organization of care service provision, including the degree of public-sector engagement in the provision of particular services, the different care providers, and the locus of care provision (institutional vs other contexts, e.g. households). Comparing two childcare-related occupations (early-education teaching and domestic service), the author argues that those two – possibly mutually reinforcing – dimensions intersect to explain differences between care workers’ labour market positions.